2018
DOI: 10.1155/2018/4651582
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Belief Network and Dempster-Shafer-Based Multiclassifier for the Pathology Stage of Prostate Cancer

Abstract: Object Pathologic prediction of prostate cancer can be made by predicting the patient's prostate metastasis prior to surgery based on biopsy information. Because biopsy variables associated with pathology have uncertainty regarding individual patient differences, a method for classification according to these variables is needed. Method We propose a deep belief network and Dempster-Shafer- (DBN-DS-) based multiclassifier for the pathologic prediction of prostate cancer. The DBN-DS learns prostate-specific anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the past few years, some predictive tools were developed to help identify the PCa risk before biopsy, such as probability table, artificial neural network, and nomogram. [12][13][14][15][16][17][18] Comparing with other tools, the nomogram could integrate different risk factors and provide an individualized estimation of PCa probability. Besides, the nomogram can be displayed graphically and easily applied in clinical practices.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, some predictive tools were developed to help identify the PCa risk before biopsy, such as probability table, artificial neural network, and nomogram. [12][13][14][15][16][17][18] Comparing with other tools, the nomogram could integrate different risk factors and provide an individualized estimation of PCa probability. Besides, the nomogram can be displayed graphically and easily applied in clinical practices.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies include analyzing medical images with AI technology to discriminate images and use them for treatments; predicting the course of a disease through various medical and health care data; developing medical devices that can support decision-making during treatments or for diagnosis; and encrypting medical data. 5 6 7 8 9 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that CNN-based models mostly focused on analyzing medical image data, with RNN architectures for sequential data analysis and AEs for unsupervised dimensionality reduction yet to be actively explored. Other deep learning methods, such as deep belief networks [ 137 , 138 ], deep Q network [ 139 ], and dictionary learning [ 140 ], have also been applied to biomedical research but were excluded from the content analysis because of low citation count. As deep learning is a rapidly evolving field, future biomedical researchers should pay attention to the emerging trends and keep aware of state-of-the-art models for enhanced performance, such as transformer-based models, including bidirectional encoder representations from transformers for NLP [ 141 ]; wav2vec for speech recognition [ 142 ]; and the Swin transformer for computer vision tasks of image classification, segmentation, and object detection [ 143 ].…”
Section: Discussionmentioning
confidence: 99%